Effects of Ginkgo biloba Extract on Cultured Human Retinal Pigment Epithelial Cells under Chemical Hypoxia. (21st June 2013) - Oh, Jong-Hyun; Oh, Jaeryung; Togloom, Ariunaa; Kim, Seong-Woo; Huh, Kuhl
Abstract: Purpose : To investigate the effects of Ginkgo biloba extract (GBE) on expression of hypoxia-inducible factor (HIF)-1α and vascular endothelial growth factor (VEGF) in retinal pigment epithelial (RPE) cells under chemical hypoxia. Materials and Methods : RPE cells (ARPE-19) were cultured in either untreated media (control group), media treated with 200 μM cobalt chloride (hypoxia group) or media treated with both 200 μM cobalt chloride and 100 μg/ml GBE (hypoxia + GBE group) for various amounts of time. HIF-1α and VEGF expression were compared between groups. HIF-1α and VEGF messenger RNA (mRNA) were quantified using real-time polymerase chain reaction (PCR). HIF-1α of extracted nuclei and VEGF of the media were quantified using enzyme-linked immunosorbent assay (ELISA). The expression of HIF-1α was also assessed with Western blot and immunocytochemistry. Results : HIF-1α mRNA, VEGF mRNA, HIF-1α and VEGF levels were higher in the hypoxia group compared with the control group; however, real-time PCR revealed decreased expression of HIF-1α mRNA and VEGF mRNA in the hypoxia + GBE group compared with the hypoxia group. In the ELISA, the HIF-1α and VEGF protein concentrations also decreased with GBE treatment. Western blot and immunostaining showed that the intensity of HIF-1α signals in the hypoxia + GBE group was lower than that of the hypoxia group. Conclusion : GBE reduced HIF-1α and VEGF expression in RPE cells cultured under chemical hypoxia in vitro .